G359 The diagnosis, management and outcomes of paediatric eosinophilic oesophagitis: a five-year retrospective analysis of the west of scotland population. (27th April 2015) - Goddard, M; Flynn, DM; Penman, D; Barclay, AR; Duncan, H; Russell, RK; Hansen, R
Abstract : Background: Eosinophilic oesophagitis (EO) is a recently described allergic condition characterised by oesophageal dysmotility with progression to stricture formation in severe cases. Diagnosis is histological, based on >15 per high-powered field in oesophageal biopsies. Treatment options remain limited to dietary modification (including elemental feeds), proton pump inhibitors (PPI) and topical/systemic steroids. There is sparse population data on the condition. To report demographic data on children with EO, establish the current burden of disease and review effectiveness of treatments with clinical and histopathological outcomes. Methods: All patients diagnosed with EO between 2008–2013 in RHSC Glasgow were retrospectively identified by joint review of all oesophageal histopathology reports (n = 1060) with a Consultant Paediatric Pathologist (DP) and findings correlated with clinical symptoms, treatment and outcomes. Data was analysed using Microsoft Excel 2007 and SPSS version 22.0. Results: Within the West of Scotland 30 children (mean age 9.1, range 0.7–15.2) were diagnosed with EO between January 2008 and May 2013 with no obvious increase in annual incidence. 22 (73%) were male. The most common presenting symptoms were abdominal pain (43%), vomiting (37%) and dysphagia (33%), with food bolus obstruction in 27%. Most (77%) had concurrent atopic disease. At diagnosis the mean number of oesophageal eosinophils per high-powered field was 61, ascertained with a mean of 5 biopsies from 3 different oesophageal regions. The mean peripheral eosinophil count at diagnosis was 1.8 (range 0.0–27.0). PPIs were clinically effective in 19/21 (70%) patients and 14/16 showed histological improvement. All 17 patients receiving dietary therapy demonstrated clinical improvement and 14/15 showed histological improvement; 11 (40%) had topical steroids, clinically effective in 10/11 patients with 7/9 showing histological improvement. However, 4 (13%) progressed to oral steroids. There was considerable overlap between treatments. At one year follow-up 93% were clinically improved and 86% showed endoscopic improvement. Conclusions: The total numbers of patients diagnosed was surprisingly small. Whilst treatment with PPI is effective, most patients also required dietary or steroid therapy. A significant number required oral steroids. A departmental guideline is being developed on the basis of these results and further work is required to establish frequency of repeat endoscopy.